FAIR VALUE ILLUSTRATED IN OMFP 1802/2014 - Valentin Gabriel CRISTEA (Challenges of the Knowledge Society, 2016)
The fair value of assets is calculated from the evidence of market data through an assessment by authorized appraisers, according to law. The fair value of tangible assets is calculated based on their market value, based on information that we would use market participants in setting asset price. The fair value is determined by reference to one of the following: a) market value, for those financial instruments for which a reliable market easily identify. b) a value resulting from models and generally accepted valuation techniques for financial instruments that can not easily identify a reliable market, so these models and valuation techniques to ensure a reasonable approximation of market value.